The Eduk Motif in Faturika Weaving: Symbolizing Traditional Leadership Through the Fourth Principle of Pancasila - Antonius Bere; Selsus Terselly Djese (FKIP, Universitas Palangka Raya, 2026)
Woven textiles are cultural artifacts imbued with rich symbolism and meaning. Among the values they embody are ethical principles that portray the noble character of an ideal leader. In Indonesia's contemporary socio-political landscape, however, leadership has been challenged by persistent problems, including corruption, abuse of power, and arbitrary governance, as reflected in numerous cases involving public officials. This study explores the cultural dimension of leadership by examining the symbolism and meaning of the Eduk motif in order to rediscover the noble values inherited from ancestors and embedded in cultural leadership artifacts, particularly the Eduk motif found in the woven textiles of Faturika, Belu Regency, East Nusa Tenggara Province, Indonesia. Employing a qualitative interpretive approach, the study reveals that the Eduk motif embodies the virtues of leadership through its symbolic representation of the antlion and the Timor python. These leadership values converge with the Fourth Principle of Pancasila, particularly the principle of wisdom in deliberation and representation. The findings suggest that the ethical values embedded in the educational motif can serve as a cultural foundation for strengthening the moral character of leaders at both the local and national levels.